Evaluation on fire resistance of composite segmental lining for shield tunnel. (January 2023) - Zhang, Gaole; Zhang, Wenjun; Zhang, Xinxin; Shangguan, Dandan; Ling, Tonghua; Guan, Linxing
Highlights: A 3D refined FEM was proposed to evaluate fire resistance of composite segment. The bearing capacity of composite segment was detected at different temperatures. The ductility of composite segmental joint may be greatly decreased due to fire. A high-temperature interlayer appears owing to the different thermal conductivity. The concrete damage was mainly caused by temperature rise and extra deformation. Abstract: This paper developed a FEM modeling to evaluate the composite segmental lining's fire resistance by simulating the thermo-mechanical behavior under the fire conditions. The mechanical and thermal properties related to concrete and steel were selected and introduced in detail. FE models of the single composite segment, segmental joint, and the full segmental lining were then established in ABAQUS. The verification of the models was conducted compared with the results from three experiments. Based on the calibrated FE models, the bearing capacity was first investigated for all three models at normal temperature and after the fire. The temperature distribution and deformation modes were subsequently examined. An in-depth discussion was conducted on the concrete damage and the corresponding protection methods. A comparison was finally carried out to detect the fire resistance between the plain concrete segment and the composite segment. The results showed that both the bearing capacity and the composite segmental joint's flexibility might significantly decrease due to the fire loading. The concrete damage was mainly caused by the rising temperature and the corresponding deformation of the whole lining ring with the expansion of different components during the fire. The restraint provided by the covered steel plates to the concrete inside led to the enhancement of the fire resistance for the composite segment. The proposed FEM model can be applied to simulate the thermo-mechanical behavior of other types of composite structures with reasonable material properties.